2009
DOI: 10.1007/s00586-009-1148-9
|View full text |Cite
|
Sign up to set email alerts
|

The ipsilateral lamina–pedicle angle: can it be used to guide pedicle screw placement in the sub-axial cervical spine?

Abstract: Pedicle screws in the sub-axial spine are infrequently used because of concerns over their safety and difficulty in placement, despite their superior pullout strength. In the sub-axial cervical vertebrae, we have observed that the lamina appears to project at right angles to the ipsilateral pedicle axis. The aim of this investigation was to confirm the lamina orientation as a reliable landmark for pedicle screw placement. 80 digital cervical spine CT were analysed. The angle formed by the ipsilateral outer lam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…There have been some reports on the methods of subaxial CPS placement, 1 , 10 , 14 - 27 but to our knowledge, this is the first radiological and workshop report on CPS insertion via the nAA. As the EP, length of the screw, and sagittal and transverse trajectory angles are concerned, the nAA-CPS technique is technically different from the classic CPS technique proposed by Abumi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some reports on the methods of subaxial CPS placement, 1 , 10 , 14 - 27 but to our knowledge, this is the first radiological and workshop report on CPS insertion via the nAA. As the EP, length of the screw, and sagittal and transverse trajectory angles are concerned, the nAA-CPS technique is technically different from the classic CPS technique proposed by Abumi.…”
Section: Discussionmentioning
confidence: 99%
“…Hacker et al 28 employed the contralateral lamina as a reliable guide for CPS placement via the AA, as they found that the axis of the pedicle in the transverse plane was almost always parallel with the contralateral lamina. Bayley et al 18 reported that the angle between the ipsilateral lamina and axis of the pedicle was in the transverse plane and found that the angle formed by the posterior cortex of the lamina and ipsilateral pedicle showed a high level of consistency ranging from 96° to 87°, suggesting that the orientation of the lamina forms a useful reference plane for classical CPS insertion. In our study, we found that the line connecting the EP and conjunction of the lamina and spinal process was almost perpendicular to the nAA of the pedicle in the transverse plane (T-angle with an average value of 92°).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of SCPS insertion was proposed by Abumi et al . [ 3 ] Pedicle screw fixation in the cervical spine due to three column stabilization provides significantly greater rigidity compared with lateral mass screw fixation,[ 4 5 6 7 ] this is most important in cases of poor bone quality. [ 4 ] Numerous biomechanical studies show the reliability of the SCPS fixation,[ 4 6 8 9 ] nevertheless many authors note high risk of neurovascular injury.…”
Section: Discussionmentioning
confidence: 99%
“…The usage of navigational systems and laminoforaminotomy reduces the risk of malposition. [ 2 5 7 12 14 22 23 24 25 26 27 28 29 30 31 32 33 ] Comparison of three insertion techniques (anatomical landmarks, laminoforaminotomy, and computer-assisted navigation) showed that the critical malposition accounted for 65.6%, 39.6%, and 10.6%, respectively. [ 34 ] However, other authors determined that the risk of screw malposition in the computer-assisted navigation is higher than without it,[ 1 4 ] perhaps due to the fact that CT-based navigation cannot provide real-time navigation and intraoperative changes of spinal alignment can appear during the patient positioning, flexion or extension, rotation, and torsion of the neck.…”
Section: Discussionmentioning
confidence: 99%
“…There is no defined standard technique 3,4,12) . To avoid screw malposition and complications, navigation-assisted surgery, sensing and seeing the pedicle with micro-laminotomies and careful analysis of preoperative computed tomography (CT) are recommended 5,7,30) .…”
Section: Introductionmentioning
confidence: 99%